Anticoagulation for Atrial Fibrillation in Acute Coronary Syndrome Survivors Reduces Major Cardiovascular Events and Mortality - Łukasz Pyka MD, PhD; Bartosz Hudzik MD, PhD; Stanisław Bartuś MD, PhD; Paweł Buszman MD, PhD; Marek Gierlotka MD, PhD; Wojciech Wojakowski MD, PhD; Jarosław Hiczkiewicz MD, PhD; Andrzej Kleinrok MD, PhD; Michał Skrzypek MD, PhD; Wiktor Kuliczkowski MD, PhD; Mariusz Gąsior MD, PhD (SAGE Publishing, 2023)
Introduction The prevalence of atrial fibrillation (AF) in acute coronary syndrome (ACS) patients is increasing. Data on outcomes of anticoagulation in ACS patients with AF are lacking. Objectives The aim of our study was to investigate the prevalence of stroke, myocardial infarction, bleeding complications, and all-cause mortality in this population. Patients and methods PL-ACS and AMI-PL registries gather an all-comer population of ACS patients in Poland, exceeding half a million records. We have selected ACS survivors with concomitant AF on admission, divided them into subgroups with regard to the administered anticoagulation, and followed up with them for a 12-month period ( n  = 13,973). Subsequently, groups were propensity score matched for age, sex, ejection fraction, diabetes, heart failure, renal impairment, and type of ACS. Results The study population was divided with regard to the administration of anticoagulation. Anticoagulation was prescribed in 2,466 patients (17.6%). The (D)OAC+ patients were younger; however, comorbidities were more prevalent in this group. The 12-month follow-up showed that the (D)OAC+ patients had significantly lower rates of all-cause mortality, myocardial infarction, and ischemic stroke, with no significant increase in bleeding events. After matching, the study groups consisted of 2,194 patients each and showed no differences in baseline characteristics. The outcomes of the 12-month observation were similar to the findings before matching. Conclusions This all-comer national registry analysis shows that the use of guideline-recommended therapy and anticoagulation in ACS survivors with AF is associated with a lower rate of all-cause mortality, recurrent myocardial infarction, and ischemic stroke.